Model Analysis of Sandstone Tunnel Cracking Based on Fracture Mechanics Theory and Sensor Testing Technology Research. (14th February 2022) - Jin, Hu; Gao, Bo; Shen, Yusheng
Abstract : In this paper, we survey sandstone tunnels using sensor testing technology and conduct an in-depth analysis and research on the model of sandstone tunnel cracking based on the theory of fracture mechanics. This paper systematically investigates the static mechanical properties, energy evolution and distribution law, acoustic emission monitoring, and digital image correlation methods of intact and jointed rock chamber enclosures (including parallel jointed rock chamber enclosures and cross jointed rock chamber enclosures) under static loads, based on physical simulation test methods and combined with other technical means such as acoustic emission monitoring and digital image correlation methods. In this paper, the effects of parallel and cross-joint angles on the static mechanical properties, energy evolution and distribution, acoustic emission variability, progressive destabilization, and their mechanisms are compared and analyzed. This paper takes fiber Bragg grating (FBG) sensing theory and technology research as a breakthrough, relies on major underground engineering geohazard model tests, and proposes a grating spectral reconstruction theory based on the wavelength position constraint of the spectral center and its improvement based on an in-depth analysis of the influence of fiber grating intrinsic parameters and strain distribution on the reflection spectral properties. Based on an in-depth analysis of the influence of spectral center wavelength location and strain distribution on the reflectance spectral properties, we propose the grating spectral reconstruction theory based on the spectral center wavelength location constraint and its improved genetic algorithm optimization method; realize the fast and accurate identification and rejection of the melancholy effect of fiber grating; propose the sensor numerical simulation optimization design method; develop the high sensitivity seepage pressure sensor, new strain sensor, target flow sensor, microdisplacement sensor, and multipoint displacement sensor; and build a large capacity, multi-parameter fiber grating real-time monitoring network.